Efficient Charge Transfer in MAPbI3 QDs/TiO2 Heterojunctions for High-Performance Solar Cells - Hua Li; Chao Ding; Dong Liu; Shota Yajima; Kei Takahashi; Shuzi Hayase; Qing Shen (Nanomaterials, 2023)
Methylammonium lead iodide (MAPbI3) perovskite quantum dots (QDs) have become one of the most promising materials for optoelectronics. Understanding the dynamics of the charge transfer from MAPbI3 QDs to the charge transport layer (CTL) is critical for improving the performance of MAPbI3 QD photoelectronic devices. However, there is currently less consensus on this. In this study, we used an ultrafast transient absorption (TA) technique to investigate the dynamics of charge transfer from MAPbI3 QDs to CTL titanium dioxide (TiO2), elucidating the dependence of these kinetics on QD size with an injection rate from 1.6 × 1010 to 4.3 × 1010 s−1. A QD solar cell based on MAPbI3/TiO2 junctions with a high-power conversion efficiency (PCE) of 11.03% was fabricated, indicating its great potential for application in high-performance solar cells.